Linking Human Capital, Information Technology and Material Handling Equipment to Warehouse Operations Performance - Azahari Ramli; Muhammad Shukri Bakar; Buba Musa Pulka; Najafi Auwalu Ibrahim (International Journal of Supply Chain Management, 2017)
Human capital, information technology and material handling equipment are considered as the vital resources needed by organization in operating warehouse effectively and efficiently. However, there are very few previous studies that have proved conclusively the relationships between these resources and warehouse operation performance. Hence, this study is conducted to determine these relationships in order to explain better how these resources should be given priority. A set of questionnaires were developed for a population of 1,589 licensed manufacturing warehouses in Peninsular Malaysia. A total of 800 warehouse managers participated in the study. The data were collected via mail and 102 valid responses were analysed. The study found that all these resources had positive and significant relationship with warehouse operations performance. The study concluded that human capital should be given high priority in the warehouse operations to enable firms achieve high performance.